A study of nurses' observance rate of hygienic principles and nosocomial infections control - Faraji, Reza; Mirzaei, Samaneh; Eftekhari, Adel; Lahiji, Azam Pourghaffari; Bamakan, Mohammad Hassan Mondegari; Rad, Hamid Kabiri (International Journal of Research in Medical Sciences, 2016)
Background: Health-care personnel's familiarity with infection control methods and pathogen transmission channels play a determining role in reducing nosocomial infections. This study aimed at investigating the nurses' performance in observing hygienic principles and nosocomial infections control. Methods: This descriptive cross-sectional study was conducted on 34 nurses working at Afshar Hospital in Yazd, Iran in 2016. Nurses' performance on infections prevention was surveyed via a checklist using self-reporting by nurses. The gleaned data were analyzed using independent t-test and ANOVA. Results: Our findings suggested that 69.5% of nurses had moderate performance on nosocomial infections control with regard to themselves, 63.2% had it with regard to patients, and 71.5% had it with regard to hospital setting. Also, there was a significant correlation between performance quality and nurses' working experience (P=0.01), on the one hand, and participation in an orientation workshop (P=0.001), on the other hand. Conclusions: Based on our findings, it is rendered as mandatory for hospital authorities to provide the required conditions for improving nurses' awareness and performance with regard to observing the hygienic principles and nosocomial infections control.